(untitled) (Proceedings of International Conference on BioScience and Biotechnology, 2017)
Environmental tobacco smoke (ETS) is the main cause of second hand smoking (SHS) induced disease conditions such as chronic obstructive pulmonary disease (COPD), lung cancer, vascular cancer and other types of cancers. It was estimated by the Health and Social Care Information Center (HSCIC) in UK that in the year 2016, 16 million people worldwide between the ages of 16 - 35 years died of smoking related diseases. Hence, different analytical techniques based on mass spectrometry (MS) and chromatography were developed, to detect the presence of tobacco metabolites in body fluids. These tobacco biomarkers in different body fluids could be used to correlate the level of ETS exposure. Among all the tobacco metabolites, cotinine was studied to be the most reliable biomarker, since it does not get affected by other environmental factors and it has along half-life f 17 hours. Therefore, by studying the levels of SHS, smoking cessation programs in public places like schools, parks and public transports could be reinforced in order to protect the innocent lives who are being exposed to tobacco smoke. This review mainly focuses on the detection of cotinine in saliva, serum, urine and hair. In conclusion, it was evident that cotinine detection in hair was the most reliable biological matrix to detect ETS exposure in passive smokers.